HIGHER EDUCATION’S CONTRIBUTION INTO ECONOMIC PERFORMANCE AND INNOVATIVENESS OF LATVIA: EXPLORATORY RESEARCH - Stankevičs, Aivars; Ignatjeva, Svetlana; Meņšikovs, Vladimirs (Economic Annals, 2014)
A detailed investigation of higher education’s contribution to economicnperformance and innovativeness inLatvia is necessary because of contradictory facts in the socio-economic reality of Latvian higher education. Despite the fact that investment in theLatvian higher education system results in high participation, the economic and innovation returns, i.e., the profitability of the resulting highly educated labour force, are low. The analysis of the literature has shown that there are other factors that determine higher education’s contribution to economic performance and innovativeness and enable highly skilled specialists to potentially turn their knowledge into innovation and national income; e.g., the quality of higher education and the level of technological development in business. We conducted an empirical analysis of a set of indicators that are potentially significant to economic performance and innovativeness, and concluded that, first, higher education’s contribution to economic performance and innovativeness differs depending on the stage of the country’s economic development; and second, that a country’s ability to attract and retain talented people becomes more significant at each stage of economic development. In Latvia both theability to attract and retain talented people and the level of technological development are poorly developed,which results in low economic and innovative returnsfroma relatively large number of highly skilled specialists.